2020
DOI: 10.1096/fj.201900125rr
|View full text |Cite
|
Sign up to set email alerts
|

Robo4‐mediated pancreatic endothelial integrity decreases inflammation and islet destruction in autoimmune diabetes

Abstract: In Type 1 Diabetes Mellitus (T1DM), leukocyte infiltration of the pancreatic islets and the resulting immune-mediated destruction of beta cells precede hyperglycemia and clinical disease symptoms. In this context, the role of the pancreatic endothelium as a barrier for autoimmunity-and inflammation-related destruction of the islets is not well studied. Here, we identified Robo4, expressed on endothelial cells, as a regulator of pancreatic vascular endothelial permeability during autoimmune diabetes. Circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Due to excessive inflammatory cytokines play a crucial role in the development and progression of diabetes, [ 24 ] we next to evaluate the effect of rLZ‐8 on the expressions of TNF‐α, IL‐1β and IL‐10. As shown in Figure 4, the levels of TNF‐α and IL‐1β in pancreas and serum were significantly increased after STZ treatment as compared to the control group, while the level of IL‐10 in STZ group was also markedly reduced (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Due to excessive inflammatory cytokines play a crucial role in the development and progression of diabetes, [ 24 ] we next to evaluate the effect of rLZ‐8 on the expressions of TNF‐α, IL‐1β and IL‐10. As shown in Figure 4, the levels of TNF‐α and IL‐1β in pancreas and serum were significantly increased after STZ treatment as compared to the control group, while the level of IL‐10 in STZ group was also markedly reduced (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The SsoFast EvaGreen Supermix (BioRad, Hercules, CA, USA) was used to perform qPCR on an iQ5 Bio-Rad cycler system. The calculation of the relative mRNA expression was performed according to the ∆∆Ct method [42] by using the expression of eukaryotic translation elongation factor 2 (ETEF2) for normalization among samples [43,44].…”
Section: Rna Isolation and Qpcrmentioning
confidence: 99%
“…Mice lacking Robo4 are viable and show slightly increased vascular permeability under basal conditions. 22,28,29) In several disease models, such as those of hypoxia-induced retinopathy, 22) cancer, 24) diabetes, 30) and endotoxemia, 29,31) studies have shown that lack of Robo4 leads to more severe vascular leakage. Robo4 stabilizes endothelial permeability by regulating both adherens junctions and tight junctions in endothelial cells.…”
Section: Robo4 Suppresses Vascular Leakage Under Pathological Conditionsmentioning
confidence: 99%
“…Robo4 stabilizes endothelial permeability by regulating both adherens junctions and tight junctions in endothelial cells. 29,32,33) Adherens junctions are involved in the transmigration of cancer and immune cells, [34][35][36] and lack of Robo4 enhances lung metastasis of cancers 24,37) and diapedesis of immune cells. 29) In vitro studies have shown that Robo4 suppresses endothelial hyperpermeability induced by various stimuli such as vascular endothelial growth factor (VEGF), 22,38) interleukin-1β (IL-1β), 31) tumor necrosis factor α (TNF-α), 29,31) and histamine.…”
Section: Robo4 Suppresses Vascular Leakage Under Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation